2020
DOI: 10.3389/fvets.2020.00466
|View full text |Cite
|
Sign up to set email alerts
|

Complex Circulation of Foot-and-Mouth Disease Virus in Cattle in Nigeria

Abstract: Nigeria is a large densely populated country in West Africa. Most of its livestock is raised in a pastoralist production system with typical long distance migration in search of water and feed. As the demand for animal products largely exceeds the domestic production, large numbers of livestock are imported from neighboring countries without sanitary restrictions. In Nigeria, foot-and-mouth disease virus (FMDV) serotypes O, A, and Southern African Territories (SAT)2 are endemic for a long time. Clinical outbre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…The obtained FMD viruses (FMDVs) were characterized and compared with previously characterized viruses from Burundi—if available—and neighboring countries. In one community of Cibitoke province, FMDVs of the serotypes A and SAT2 were isolated, confirming previous findings that in sub-Saharan Africa different FMD virus strains can circulate at the same place at the same time [ 9 , 10 , 11 ]. The isolated viruses were of the same topotypes as contemporary FMDVs from Uganda, Kenya, and Tanzania.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The obtained FMD viruses (FMDVs) were characterized and compared with previously characterized viruses from Burundi—if available—and neighboring countries. In one community of Cibitoke province, FMDVs of the serotypes A and SAT2 were isolated, confirming previous findings that in sub-Saharan Africa different FMD virus strains can circulate at the same place at the same time [ 9 , 10 , 11 ]. The isolated viruses were of the same topotypes as contemporary FMDVs from Uganda, Kenya, and Tanzania.…”
Section: Discussionsupporting
confidence: 84%
“…There are seven pools described [ 7 ] and Burundi, where the current study was conducted, belongs to pool 4 (Eastern Africa), with FMDV circulating serotypes O, A, SAT1, SAT2, and SAT3 [ 8 ], and is situated at the border with neighboring pool 5 (Western/Central Africa). FMD is endemic in most parts of Africa and the epidemiological situation is complex due to marked differences in the geographic distribution of serotypes, simultaneous presence of different serotypes and topotypes in the same region, high intratypic variation, and the presence of wildlife that can act as a reservoir [ 9 , 10 , 11 ]. In the ten-year period before the sampling year of this study (2016), multiple topotypes from FMDV serotypes O, A, SAT1, SAT2, and SAT3 were reported in Africa [ 12 ], with the last report of serotype C in 2004 [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Skin biopsies or nodules for virus isolation should preferably be collected within the first week of the occurrence of clinical signs (Davies, 1991). In contrast to viruses such as Foot and mouth disease virus (FMDV), where sequencing of a part of the genome like VP1 can be enough to determine the origin of the virus (Ularamu et al., 2020), this is not possible for LSDV. Sequencing of three to five different genes (Lamien et al., 2011; Agianniotaki et al., 2017) or Whole genome sequencing (WGS) of the LSDV can help to compare the virus with recently circulating viruses in other countries or regions (Mathijs et al., 2020) and with vaccine viruses (Mathijs et al., 2016).…”
Section: Assessmentmentioning
confidence: 99%
“…Serotypes O, A, SAT 1 and SAT 2 have been isolated and characterised from cattle samples in Nigeria [7,[10][11][12]. These four serotypes belong to diverse topo-/genotypes and are phylogenetically related to strains circulating in West, Central and Northern Africa [8,11,13,14].…”
Section: Introductionmentioning
confidence: 99%